Safeguarding civility : sodomy, class and moral reform in early nineteenth-century England. - Cocks, H.G. (Oxford GB: Oxford University Press)
Aborda el tema de la seguridad civil y reforma moral en Inglaterra durante el siglo XIX.
Keywords: INGLATERRA; HISTORIA; SEGURIDAD CIUDADANA; MORAL